N -glucosylation of indole-3-acetyl amino acids modulates auxin metabolism and growth traits in Oryza sativa - Anna Zenji; Kimihiko Hata; Shoji Segami; Nobue Makita; Mikiko Kojima; Mika Yoshino-Kida; Keisuke Nagai; Motoyuki Ashikari; Kazuki Matsubara; Masahiro Yano; Shuichi Fukuoka; Ken-Ichiro Hayashi; et al. (Proceedings of the National Academy of Sciences, 2026)
Dynamic regulation of auxin (indole-3-acetic acid; IAA) levels is crucial for proper plant growth and development and is finely regulated through biosynthesis, transport, metabolic inactivation, and signal transduction. While O -glucosylation of IAA is well established, the physiological significance of N -glucosylation pathways acting on IAA-amino acid conjugates remains largely unexplored. Here, we identify a UDP-glucosyltransferase in rice ( Oryza sativa ), designated IAAspGT, that catalyzes the N -glucosylation of indole-3-acetyl (IA) amino acid conjugates. Functional analysis revealed that natural allelic variants of IAAspGT differ markedly in enzymatic activity, with the high-activity allele prevalent in indica and the low-activity allele in japonica cultivars. Mutational analysis identified key residues within the glucose-accepting substrate-binding domain that account for this variation. A metabolic perturbation experiment demonstrated that IAAspGT competes with the DAO-mediated oxidation, thereby affecting active auxin levels. Plants harboring the high-activity allele exhibited enhanced root elongation under nutrient-deficient conditions and altered growth allocation between the panicle and other above-ground organs. Haplotype analysis indicated that the high-activity allele is ancestral and widely retained in the wild relatives. These findings establish IA-amino acid N -glucosylation as a previously overlooked metabolic branch that modulates auxin availability and contributes to environmental responses and growth plasticity in rice.